Performans Anak Hasil Persilangan Induk Sapi Bali dengan Beberapa bangsa Pejantan di Kabupaten Batanghari Provinsi Jambi - Depison Depison (Jurnal Agripet, 2010)
Bali calf performance hybrid with some of the Bulls In Batanghari District, Jambi ProvinceABSTRACT. This study aimed to find out Bali calf performance hybrid with some of the males in Batanghari District Jambi Province. Variable of this research is the body Weight (age 205 days), weight age one year (365 days) and body size. The method used in this study was to reveal the census data on all the posts that do IB Bali cattle crossing with Simmenthal, Limousin, Brahman, PO and Bali vs bali. Comparison of body weight and one year old weight between the offspring Bali vs Simmenthal, Bali vs Limousin, Bali vs Brahman, Bali vs PO and Bali vs Bali, tested with t tests. The results of the analysis of different tests on average (t-test) show that body weight and weight Age 1 year SimBal Real Different (P 0.05) compared with LimBal, BrahBal, PoBal and BalBal. Based on the results and discussion can be concluded that, Bali cow crosses simmenthal produce offspring with a better than cow crosed Bali with Limousin, Brahman, and PO viewed from of body weight, weight of one year of age and body size.